Construct Validity of Group Resilience Measurement Scale in Indonesia - Lailatul Mubarokah; Adiyo Roebianto; Arni Sari (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2022)
Humans will always face challenges that interfere with their course of life. Their responses to face those challenges or resilience are varied, depending on environmental aspects. The discussion on resilience is used to understand the reasons why individuals can be more resistant to challenges than other individuals. The aspect that influences and forms resilience is the environment. One form of the influential environment is the environment in which humans are born or reside. The demographic characteristics of the Indonesian region are one form of the physical environment which is divided by geography (West Indonesia, Central Indonesia, and East Indonesia) and by type of administrative area (District and Municipalities). This study employed a quantitative approach to measure the construct validity of the CCRAM instrument which has been translated into Indonesian. This study involved 518 people (N = 518) as participants who came from three regions of Indonesia, namely East, Central, and West Indonesia. The research instrument was a questionnaire containing statements/items related to community resilience. After the data were collected online, Confirmatory Factor Analysis (CFA) was conducted to check the validity of each item on each dimension/construct. The results indicate that all dimensions and items were declared to meet the fit or valid criteria.